(untitled) (Perner’s Contacts, 2011)
Many traffic accidents are caused by failures in the interaction between the driver, the vehicle, and the traffic system. Thus, knowledge about these interactions is essential and this is especially true nowadays since the number of driving related interactions is increasing. The real world is of course the most realistic environment, but it can be unpredictable regarding, for instance, weather, road, and traffic, conditions. It is therefore often hard to design real world experiments from which it is possible to draw statistically significant conclusions.